The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1016/j.matchemphys.2008.09.069
|View full text |Cite
|
Sign up to set email alerts
|

Habit and morphology study on the palm-based 9,10-dihydroxystearic acid (DHSA) crystals

Abstract: Dihydroxystearic acid (DHSA) and its derivatives are hydroxyl fatty acids suitable to be used as multipurpose intermediates in the synthesis of personal care products and decorative cosmetics. In Malaysia, DHSA has been successfully produced from palm-based oleic acid, via epoxidation with per-formic acid followed with hydrolysis of the epoxide. The objective of this paper is to study the crystals of DHSA produced under different crystallization conditions. The crystal habit and morphology were observed in ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…4.3 Safety characteristics of 9,10-DHSA Initial evaluation concluded that crude 9,10-DHSA was irritating to human skin whereas purifi ed 9,10-DHSA was Table 3 Effects of various parameters on 9,10-DHSA purifi cation [8][9][10][11][12][13] …”
Section: Physical Characteristics Of 910-dhsamentioning
confidence: 99%
“…4.3 Safety characteristics of 9,10-DHSA Initial evaluation concluded that crude 9,10-DHSA was irritating to human skin whereas purifi ed 9,10-DHSA was Table 3 Effects of various parameters on 9,10-DHSA purifi cation [8][9][10][11][12][13] …”
Section: Physical Characteristics Of 910-dhsamentioning
confidence: 99%
“…The water acts as a crystal glue, clumping the DHSA together into lumps with plate‐like structures that have the same crystalline axis as a base crystal and repeat themselves over and over in three dimensions. These crystal agglomerates were similar in structure as desert rose aggregates (semi‐spherical rose‐like rosette aggregates) of platy barite crystals 24,25 . The EDX spectra revealed that only carbon and oxygen were present, indicating that only DHSA was present and there were no other compounds in the DHSA crystal sample.…”
Section: Resultsmentioning
confidence: 77%
“…These crystal agglomerates were similar in structure as desert rose aggregates (semi-spherical rose-like rosette aggregates) of platy barite crystals. 24,25 The EDX spectra revealed that only carbon and oxygen were present, indicating that only DHSA was present and there were no other compounds in the DHSA crystal sample. The EDX spectra showed that there was just carbon and oxygen present, which is evidence that the DHSA crystal sample had only DHSA and no other compounds.…”
Section: Sem and Edx Spectroscopymentioning
confidence: 99%
“…Saat ini, DHSA telah sukses dihasilkan dari asam oleat berbasis kelapa sawit, melalui epoksidasi dengan asam performat (rute PFA) atau asam perasetat (rute PAA) diikuti oleh hidrolisis epoksida menggunakan katalis asam sulfat (Koay et al 2009). Peningkatan proses untuk produksi hidroksil asam lemak berbasis kelapa sawit (DHSA) telah dipatenkan oleh Ahmad et al 2009.…”
Section: Pendahuluanunclassified